Financial modelling : study and application of Singapore stocks - Nyoe, Teng Siong (2008)
Against a background of rapid developments in the local financial sector, this research attempts to educate investors about risks in investing. A model is constructed to examine the relationships between returns of a stock and six risk factors: earnings risk, leverage risk, interest rate risk, economic risk, exchange rate risk and market risk.